2022
DOI: 10.5194/hess-26-4345-2022
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning methods for flood mapping: a review of existing applications and future research directions

Abstract: Abstract. Deep learning techniques have been increasingly used in flood management to overcome the limitations of accurate, yet slow, numerical models and to improve the results of traditional methods for flood mapping. In this paper, we review 58 recent publications to outline the state of the art of the field, identify knowledge gaps, and propose future research directions. The review focuses on the type of deep learning models used for various flood mapping applications, the flood types considered, the spat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 160 publications
1
47
1
Order By: Relevance
“…The Hydraulic models of flow have been practiced forecasting rainfall, storms and tsunamis [36]. These models are also used to predict impact of climatic change [37], ocean waves [38] and floods [39]. It was observed that long term prediction models were more successful than short term prediction models in hazard prediction [40] [41].…”
Section: Related Workmentioning
confidence: 99%
“…The Hydraulic models of flow have been practiced forecasting rainfall, storms and tsunamis [36]. These models are also used to predict impact of climatic change [37], ocean waves [38] and floods [39]. It was observed that long term prediction models were more successful than short term prediction models in hazard prediction [40] [41].…”
Section: Related Workmentioning
confidence: 99%
“…Methods based on numerical modelling and multicriteria decision-analysis (MCDA) that integrate GIS and remote sensing have been proposed for zoning of food vulnerability or susceptibility maps within urban areas [8,9]. MCDA approaches, however, have the disadvantage that they rely on subjective expert knowledge and do not apply food event data, and therefore their outputs are likely to be biased and prone to error [10]. On the other hand, hydrodynamic numerical models are intrinsically limited by the discretization of the physical domain of the watershed and the governing physical equations.…”
Section: Introductionmentioning
confidence: 99%
“…ANNs have high prediction ability but cannot determine the infuence and role of the food causative factors [30]. Due to the shortcomings of the standalone algorithms, hybrid ML algorithms have been proposed for improved food susceptibility mapping [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations